2008
DOI: 10.1021/bi801302b
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Basic Protein as a “PI(4,5)P2-Modulin”: A New Biological Function for a Major Central Nervous System Protein

Abstract: The 18.5 kDa isoform of myelin basic protein (MBP) is multifunctional and has previously been shown to have structural and phenomenological similarities with domains of other membrane- and cytoskeleton-associated proteins such as MARCKS (myristoylated alanine-rich C kinase substrate). Here, we have investigated whether 18.5 kDa MBP can sequester phosphatidylinositol-(4,5)-bis-phosphate (PI(4,5)P 2) in membranes, like MARCKS and other "PIPmodulins" do. Using fluorescence-quenching and electron paramagnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 70 publications
3
50
0
Order By: Relevance
“…It is interesting to note that other PIP2 binding proteins, such as MARCKS (a member of the GAP43-like family of proteins), induce the formation of large lipid domains in a PIP2-dependent manner (Laux et al, 2000;McLaughlin et al, 2002;Gambhir et al, 2004). While our study was under review, Musse et al (2008) demonstrated by fluorescence quenching and electron paramagnetic resonance spectroscopy that MBP sequesters PIP2 in model membranes, providing independent support for our model. The binding of basic proteins (i.e., MBP) to PIP2 reduces the lateral diffusion of this lipid and may also sequester other lipids into membrane microdomains.…”
Section: Discussionsupporting
confidence: 65%
“…It is interesting to note that other PIP2 binding proteins, such as MARCKS (a member of the GAP43-like family of proteins), induce the formation of large lipid domains in a PIP2-dependent manner (Laux et al, 2000;McLaughlin et al, 2002;Gambhir et al, 2004). While our study was under review, Musse et al (2008) demonstrated by fluorescence quenching and electron paramagnetic resonance spectroscopy that MBP sequesters PIP2 in model membranes, providing independent support for our model. The binding of basic proteins (i.e., MBP) to PIP2 reduces the lateral diffusion of this lipid and may also sequester other lipids into membrane microdomains.…”
Section: Discussionsupporting
confidence: 65%
“…Myristoylated alanine-rich C-kinase substrate ( MARCKS ) is an actin filament crosslinking protein, which plays a role in vesicular trafficking to the myelin sheet in mature oligodendrocytes. The regulation of PI(4,5)P2 by MARCKS has been suggested to play a role in the outgrowth of membranous cellular processes in mature oligodendrocytes 32 . Previous studies have found that MARCKS mRNA levels increase as oligodendrocytes mature, suggesting developmental regulation of this protein 33 .…”
Section: Resultsmentioning
confidence: 99%
“…An obvious factor to consider is the membrane lipid composition; the negatively charged cytoplasmic leaflet and the high cholesterol content of myelin are most probably in a delicate balance with the rest of the different lipid species, as shown by experimental disease models 9, 49, 65 . The high abundance of cholesterol has a major impact on membrane fluidity as well as myelin development 30, 66, 67 , likely being a key requirement together with various phosphoinositides 6870 to provide a suitable physiological medium for membrane-embedded proteins, including MBP. The stability of the MDL, the condition of MBP within it, and the post-natal myelinating machinery should be taken into account when it comes to understanding and possibly treating demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%